Techniques Applied In Teaching Speaking At The Fourth Semester Of English Department Of Widya Dharma University In 2012/2013 Academic Year - Dara, Wida Datu Dear, Drs. Djoko Srijono, M.Hum, Dra. Dwi Haryanti, M.Hum (2013)
This research paper is intended to describe the techniques applied in teaching speaking in speaking class of fourth semester of English Department at Widya Dharma University. The sources of the data are the lecturer and the students of fourth semester of English Department at Widya Dharma University. In this research paper, the writer uses two instruments in collecting the data, namely: observation and interview. In collecting the data, the writer focuses on the objective of learning, the material and the type of syllabus used in Widya Dharma University, the method of teaching (procdure classrooom and teaching techniques), media for teaching speaking, teacher roles, and students roles that applied in Widya Dharma University, and the strenght and the weaknesses of the method used. Based on the data analysis, the writer finds the techniques apllied in speaking class of fourth semester of English Department at Widya Dharma University as follows: (a). The techniques used in speaking IV is discussion. The lecture manages the class into two groups there are group A and B. It used in order to make the students active and be able to speak. (b). Discussion techniques is very suitable to increase students ability in speaking. They can speak freely and communicate with their friends to solve the difficulties (c).The goal of teaching speaking is to increase stuedents' oral proficiency, oral competence, grammatical rules, pronunciation and some aspect that related to oral skills,(d). The material used is freely from the internet that appropriate with the theme. The material is taken from internet and given every meeting. The material is related to the recently topic, current issues, article, phenomenon and their environment. (e).The syllabus based on the university convention that has been legalized by facult. The syllabus is one of guided to develop the material. The syllabus is designed to make the students active in speaking English. (f).In Teaching-Learning Process, the procedure of classroom are divided in to 5 steps, there are opening, brief reflection, explanation, discussion (presentation), evaluation (closing).(g).The media of teaching speaking IV in Widya Dharma University are movie, laptop, article. (h).The teacher's role is a facilitator and the student's role is as a center of the classroom.The strenght of discussion techniques are the students can speak up freely and they can encourage each other. But it also has weaknesses, they are the students who are active will be more active, the students who inactive will be more inactive , and the betterment of grammar rule run slowly.